Pemanfaatan TikTok sebagai Alat Inovatif dalam Pembelajaran Akidah Akhlak: Sebuah Tantangan Kreatif di Era Digital - Purnama, Rizky Wahyu Widi; Perawiranegara, Djamaluddin (Lembaga Yasin AlSys, 2024)
The integration of technology in education has become a crucial component, enhancing the learning process and adapting to contemporary needs. The background of utilizing technology in education encompasses various essential aspects. This study employs the library research method, which involves examining literature sources such as books, notes, and reports from previous research to gather pertinent data related to the research topic. Technology's role in education has evolved into an indispensable element, enhancing the learning journey and aligning with the current era. Library research, a method relying on literature sources like books, notes, and reports from past research, is instrumental in collecting relevant information. Educators are urged to judiciously incorporate the use of TikTok, considering school policies, and striking a balance between leveraging its positive aspects and mitigating potential risks. The adoption of TikTok in Akidah Akhlak learning yields innovative benefits, such as heightened learning motivation, active student engagement, and creative utilization of educational media. Nevertheless, challenges, including restricted access and adverse influences, necessitate careful consideration. Educators must approach the integration of TikTok thoughtfully, adhering to school policies and implementing risk-mitigation strategies. A well-devised strategy and a comprehensive approach are crucial to ensuring that TikTok serves as an effective and secure tool in Akidah Akhlak learning.